PENERAPAN PSAK NO. 23 PADA PROSEDUR PENGAKUAN PENDAPATAN DI PERUM LPPNPI CABANG SURABAYA - Siti Maimunah; Rika Yuliastuti (PUTRA JAWA PUBLISHER, 2024)
The objective of this study is to analyze the application of PSAK No. 23 in revenue recognition procedures at Perum LPPNPI Surabaya Branch, particularly in the context of contracts with customers. This research focuses on the recognition of transactions when the services offered by LPPNPI have been completed and explores the measurement of PJNP Government Regulation (PP) rates and the presentation of related profit and loss. PSAK No. 23 is the main reference in revenue recognition that is relevant for business entities, including income from services provided. This study uses a qualitative approach by interviewing relevant staff and analysing documents related to payment recognition procedures. The results show that the application of PSAK No. 23 requires an in-depth understanding of the relevant accounting principles and the specific business context, especially in dealing with situations where customers contact the service after the service has been provided, the measurement of the appropriate LGAP rate, and the accurate presentation of profit or loss. The practical implication of this study is to provide guidance to Perum LPPNPI Surabaya Branch and other business entities in improving compliance with applicable accounting standards, ensuring proper measurement of PP PJNP tariffs, and transparent and accurate presentation of profit or loss in financial reports.